2022
DOI: 10.1002/mas.21819
|View full text |Cite
|
Sign up to set email alerts
|

Ion‐molecule reactions of mass‐selected ions

Abstract: Gas‐phase reactions of mass‐selected ions with neutrals covers a very broad area of fundamental and applied mass spectrometry (MS). Oftentimes, ion‐molecule reactions (IMR) can serve as a viable alternative to collision‐induced dissociation and other ion dissociation techniques when using tandem MS. This review focuses on the literature pertaining applications of IMR since 2013. During the past decade considerable efforts have been made in analytical applications of IMR, including advances in one of the major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 250 publications
0
3
0
Order By: Relevance
“…In most cases, these fragment ions can correspond to a large number of conceivable structures. Structural information on gas-phase ions can be obtained, for example, using ion–molecule reactions that allow to identify functional groups. Another technique that has been extensively used to determine structures of intact ions and dissociation products is gas-phase infrared (IR) ion spectroscopy. , Gas-phase IR spectroscopy yields IR spectra of m / z -selected ions, which are characteristic of the ionic structure and reveal the presence of various functional groups. Because IR absorption of isolated ions in the gas phase reflects their quantum-chemical properties, the probed ion structures can be assigned by comparison with quantum-chemically computed IR spectra of candidate structures.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, these fragment ions can correspond to a large number of conceivable structures. Structural information on gas-phase ions can be obtained, for example, using ion–molecule reactions that allow to identify functional groups. Another technique that has been extensively used to determine structures of intact ions and dissociation products is gas-phase infrared (IR) ion spectroscopy. , Gas-phase IR spectroscopy yields IR spectra of m / z -selected ions, which are characteristic of the ionic structure and reveal the presence of various functional groups. Because IR absorption of isolated ions in the gas phase reflects their quantum-chemical properties, the probed ion structures can be assigned by comparison with quantum-chemically computed IR spectra of candidate structures.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7,[83][84][85][86] In this respect, gas phase experiments can serve as a fruitful source of serendipitous findings. [87] For example, it has previously been found that "rollover"-cyclometalated [88][89][90][91][92] [(bipyÀ H)Pt] + (1, bipy = 2,2'-bipyridine) is able to activate a variety of small molecules such as methane, [93] chloromethanes, [94] ethers, [95] and thioethers, [96,97] and all these reactions are unprecedented in solution. Particularly, in the ion/molecule reaction of [(bipyÀ H)Pt] + (1) with (CH 3 ) 2 S, [97] the elimination of C 2 H 4 (i. e. CÀ C-bond coupling of the two methyl groups of the neutral substrate) was quite unexpected (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the continuous progress of chemical derivatization for UFA, there are few studies on the separation of UFA based on ion mobility-mass spectrometry (IM-MS), due to the weak separation ability and poor substrate generalization. More methods have been developed for coupling with high-performance liquid chromatography-mass spectrometry (HPLC-MS) or gas chromatography-mass spectrometry (GC–MS). Unlike the chromatographic-based and fragmentation-based methods, IM-MS is expected to realize the high-throughput analysis of UFA isomers under gas-phase conditions because the conformation of the CC in UFA can significantly affect the overall molecular shape and collision cross section. Groessl et al achieved a better separation and identification of cis / trans phosphatidylcholine isomers using high-resolution, low-field multiplexed drift-tube IM-MS .…”
mentioning
confidence: 99%